Characterizing the naturally occurring sacrificial bond within natural rubber. (14th January 2019) - Fu, Xuan; Huang, Cheng; Zhu, Yong; Huang, Guangsu; Wu, Jinrong
Abstract: The influence of protein on the superior properties of NR was analyzed in term of sacrificial bonds. It was found that the presence of the naturally occurring sacrificial bond provided by protein increases the tensile strengthen and toughness, furthermore prolongs the fatigue life of NR. The superior properties of NR are due to the combine effect of the vulcanized network and the pseudo network constructed by the linked protein and other non-rubber components. The breaking down of the weak pseudo network could provide effective energy dissipation to avoid material failure. The regeneration of the pseudo network helps to preserve the sacrificial bonds, which ultimately leads to the remarkable fatigue resistance of NR. The impact of protein of the network structure is essential to its effect on the properties of NR. Graphical abstract: Natural rubber (NR) shows better mechanical properties than its synthetic counterpart, polyisoprene (PI). One widely accepted mechanism to interpret this phenomenon is the existence of naturally occurring network in NR, which is formed by linking the terminal groups of PI chains with the aggregrates of proteins and phospholipids through hydrogen or ionic bonds. However, how this naturally occurring network works to improve the mechanical properties remains largely unknown. Herein we consider that the naturally occurring network can dissociate and re-associate upon deformation, thus playing a role of sacrificial bonds to dissipate energy. To prove this speculation, we remove the free and bonded proteins from NR, and find that both these two types of proteins influence the performances of NR. The proteins has huge influence on the mechanical properties of un-vulcanized NR, while has little impact on that of vulcanized NR. However, the existence of bonded proteins provides extra energy dispassion in the vulcanized NR (S-NR) matrices, as well as prolongs the fatigue life of S-NR. The results reveal that the superior properties of NR are due to the combine effect of the vulcanized network and the pseudo network constructed by the linked protein and other non-rubber components. The breaking down of the weak pseudo network could provide effective energy dissipation to avoid material failure. The regeneration of the pseudo network helps preserving the sacrificial bonds, which ultimately leads to the remarkable fatigue resistance of NR. Highlights: sacrificial bonds; protein; pseudo network; energy dissipation.